Functional outcomes of posterior cruciate ligament tibial avulsion fractures treated with open reduction and internal fixation and screw fixation: a retrospective study - Patel, Sunny K.; Solanki, Dharmik P.; Rathod, Bhumil C. (International Journal of Research in Orthopaedics, 2026)
Background: Posterior cruciate ligament (PCL) avulsion injuries can result in significant knee instability and long-term functional impairment if inadequately treated. Open reduction and internal fixation (ORIF) is widely employed to achieve anatomical restoration and preserve the native ligament. This study aimed to evaluate the clinical and functional outcomes of ORIF in patients with acute PCL avulsion injuries. Methods: A retrospective study was conducted at a tertiary healthcare center including 30 patients treated with ORIF for acute PCL avulsion injuries between 2022 and 2025. Inclusion criteria comprised MRI-confirmed tibial PCL avulsion fractures and a minimum 12-month follow-up. Patients with chronic injuries or prior knee pathology were excluded. Functional outcomes were assessed using the Cincinnati knee rating system (CKRS), international knee documentation committee (IKDC) score, and Lysholm score preoperatively and at 12 months postoperatively. Results: The cohort consisted of 24 males (80%) and 6 females (20%), with a mean age of 34.6±11.8 years. Road traffic accidents were the most common mechanism of injury (50%). Preoperative mean scores were CKRS 46.1±7.9, IKDC 49.3±7.2, and Lysholm 14.2±4.5. At 12 months, significant improvement was observed: CKRS 84.3±5.9, IKDC 86.7±5.5, and Lysholm 93.8±6.4 (p<0.001). Conclusions: ORIF provides significant functional improvement and reliable restoration of knee stability in acute PCL avulsion injuries. Early surgical intervention combined with structured rehabilitation results in favorable one-year outcomes.